1994
DOI: 10.1139/e94-063
|View full text |Cite
|
Sign up to set email alerts
|

Possible extension of the Midcontinent Rift in west Texas and eastern New Mexico

Abstract: The Midcontinent Rift System forms one of the most prominent gravity features in North America. The recognized geophysical anomaly extends in an arc from southern Oklahoma to Lake Superior and then into southern Michigan. The Midcontinent Rift System was active between 1185–1010 Ma, as indicated in the Lake Superior region by age determinations on intrusive igneous rocks. We suggest that the period of formation of the Midcontinent Rift was also a time of extensive igneous activity in Texas and New Mexico. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 51 publications
(87 reference statements)
1
9
0
Order By: Relevance
“…Gravity lows are observed over the Anadarko and Arkoma basins, while highs are associated with the Arbuckle uplift, the southern Oklahoma aulacogen (aligned with the Wichita uplift), and the Cherokee platform in Osage County. The gravity high associated with the inferred extension of the Midcontinent coincides with a group of rounded magnetic highs and has been interpreted as Keweenawan intrusive rock (Figure c) [ Lyons , ; Luza and Lawson , ; Adams and Keller , , and references therein]. The Arkoma basin is associated with a much steeper gravity low than the Anadarko basin even though it is not as deep.…”
Section: Resultsmentioning
confidence: 99%
“…Gravity lows are observed over the Anadarko and Arkoma basins, while highs are associated with the Arbuckle uplift, the southern Oklahoma aulacogen (aligned with the Wichita uplift), and the Cherokee platform in Osage County. The gravity high associated with the inferred extension of the Midcontinent coincides with a group of rounded magnetic highs and has been interpreted as Keweenawan intrusive rock (Figure c) [ Lyons , ; Luza and Lawson , ; Adams and Keller , , and references therein]. The Arkoma basin is associated with a much steeper gravity low than the Anadarko basin even though it is not as deep.…”
Section: Resultsmentioning
confidence: 99%
“…However, this LVB extends further southward to intersect the Oklahoma Aulocogen. Adams and Keller [1993] studied the stratigraphy, the ages and lithologic properties of volcanic rocks and found strong similarities between those in western Oklahoma, Texas and eastern New Mexico with the identified MCR and suggested that the MCR may actually extend further southwest from its west limb terminus in Kansas. Their suggestions are also supported by Yarger [1985] and Nixon [1988].…”
Section: Discussionmentioning
confidence: 97%
“…Associated tectonic events might be extension that did not proceed long enough to generate significant mafic rocks, mantle heating due to upwelling or diapirism, or dextral slip (Anderson & Morrison, 2005;Bickford et al, 1986;Thomas, 2006). Additional tectonic activity may have occurred during rifting of the midcontinent 1200-1000 Ma ago; extension of this rift is suggested through southern Kansas and northwestern Oklahoma (Adams & Keller, 1994;Luza & Lawson, 1982;Lyons, 1959;Robbins & Keller, 1990).…”
Section: Geologic Backgroundmentioning
confidence: 99%